Perancangan Walk-In Closet pada Apartemen Tipe Studio untuk Wanita Karir Lajang - Diana Puspasari (Intra, 2017)
Nowadays, studio type apartment become a choice of residence for people especially for the young who start the career. It was choosen because of the practical and the space of the room that make easier for user to keep it clean. Walk-In Cloest is important things to have to fulfill her needs of dressing especially for woman. The limitation of space and a lot of dressing needs, compact furniture is needed.. Based of analysis, compact furniture can support the other activities and save space. Walk-In closet that use a playwood, things that needs to be concern are to maximize the utilization of space.